2018
DOI: 10.1002/jcb.27492
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of large‐scale deletions of the sperm mitochondrial DNA in normozoospermic and asthenoteratozoospermic men

Abstract: Our findings suggested that these large-scale deletions of mtDNA may be genetic risk factors for poor sperm quality in asthenoteratozoospermia-induced male infertility. Thus, it is necessary to understand the mechanisms behind the generation of these deletions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Defects of mtDNA in oligoasthenozoospermic patients made DNA unavailable for amplification [ 22 ]. Large-scale deletions of mtDNA were pointed to as risk factors for poor sperm quality in asthenoteratozoospermia-induced male infertility [ 23 ]. Beside mtDNA, the importance of mitochondrial membrane potential is recognized not only for spermatozoa functionality [ 24 , 25 , 26 ], but also, in combination with sperm DNA fragmentation, as standard semen parameter for the prediction of natural conception [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Defects of mtDNA in oligoasthenozoospermic patients made DNA unavailable for amplification [ 22 ]. Large-scale deletions of mtDNA were pointed to as risk factors for poor sperm quality in asthenoteratozoospermia-induced male infertility [ 23 ]. Beside mtDNA, the importance of mitochondrial membrane potential is recognized not only for spermatozoa functionality [ 24 , 25 , 26 ], but also, in combination with sperm DNA fragmentation, as standard semen parameter for the prediction of natural conception [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial morphological changes are specific for stages of spermatogenesis 26 and could explain the strong association of altered ultrastructure of mitochondria with unexplained asthenozoospermia 27 . Clinical trials showed that the mtDNA of oligo-asthenozoospermic patients present some defects that made DNA unavailable for amplification 28 and that large-scale deletions of mtDNA may be genetic risk factors for poor sperm quality in asthenoteratozoospermia-induced male infertility 29 . Numerous studies on humans pointed the importance of mitochondrial membrane potential not only for spermatozoa functionality 30 32 but also, in combination with sperm DNA fragmentation, as a superior to standard semen parameters for the prediction of natural conception 33 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 4,977 and 7,599 bp deletions of mtDNA have been related to male infertility in different populations (Kumar & Sangeetha, 2009; Talebi et al., 2018). Other large‐scale mutations such as 7436‐bp and 4866‐bp deletion have been described to be related to the possible association with male infertility (Chari et al., 2015; Gholinezhad et al., 2019; Karimian & Babaei, 2020). Therefore, the complete portrait of the molecular markers related to male infertility needs to be developed by screening the high‐risk variants in different populations to elucidate the most common genetic mutations and variations that are related to the development of male infertility.…”
Section: Discussionmentioning
confidence: 99%